Performance of different commercial layer strains in Bangladesh (Asian Journal of Medical and Biological Research, 2021)
To know the production performances of different commercial layer strains in Bangladesh, total 18,420 birds of ISA Brown, 14,790 birds of Novogen-Brown and 27,400 birds of Shavar-579 Brown were studied from 30 commercial layer farms (10 farms for each strain), which were randomly selected from the 7 different districts of Bangladesh by farm visit via a well structured questionnaire. All birds were reared in open-sided shed in cage system. The hen day egg production percentage (HDEP%), average body weight and average feed intake per day of three different strains were studied. The HDEP% of ISA Brown, Novogen-Brown and Shaver-579 Brown were 90.79±0.44%, 78.89±1.84% and 79.13±1.41% respectively, average body weight were 1877±26.4 gm, 1885±26.9 gm and 1815.5±43.9 gm respectively, average feed intake per day were 111±1.88 gm, 109.8±1.86 gm and 112.5±1.35 gm respectively. The HDEP% was higher in ISA Brown, however there were no significant difference among strains for average body weight and average feed intake per day. Finally, it is recommended that ISA Brown is more adaptable and profitable in Bangladesh than that of other strains. Further scientific study is needed to see the production performance of different commercial layer strains in farm trail with same environmental condition.Asian J. Med. Biol. Res. March 2021, 7(1): 33-39